Bruchs Membrane Opening Area Measurement in Healthy Nepalese Eyes - Kharel Sitaula, Ranju; Shah, Ganga Sagar (Journal of Nepal Health Research Council, 2024)
Background: Bruch’s membrane opening area is the circular area around the disc of Bruch’s membrane, which is devoid of Bruch’s membrane and can be assessed by capturing the retinal imaging system by Spectral-domain optical coherence tomography. BMOA can be a new landmark in analyzing the glaucomatous optic nerve head, myopic optic disc, optic neuropathy and uveitic disc edema. This is the first study from South Asia to evaluate the normal Bruch’s membrane opening area among Nepalese eyes.Methods: This hospital-based, cross-sectional, quantitative, observational study cross-sectional study was conducted in a tertiary eye care hospital in Nepal. Healthy immunocompetent Nepalese participants of both genders and different age groups were enrolled. The mean average Bruch’s membrane opening area of each eyes, the difference in Bruch’s membrane opening area between the two eyes and the gender of varying age groups were analyzed.Results: Around 162 eyes (81 participants) were analyzed. The mean age was 56.69±17.5years. The mean average Bruch’s membrane opening area of the right and left eye was 2.53±0.58 mm2 and 2.50 ±0.58 mm2. There was no significant difference in the Bruch’s membrane opening area in either eye in both genders of any age group.Conclusion: The Bruch’s membrane opening area does not differ significantly according to the laterality, gender and age group in Nepalese eyes.Keywords: Bruchs membrane opening; Bruchs membrane opening area; Nepal; optical coherence tomography.